If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10(s + 2) = 9 Reorder the terms: -10(2 + s) = 9 (2 * -10 + s * -10) = 9 (-20 + -10s) = 9 Solving -20 + -10s = 9 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + -10s = 9 + 20 Combine like terms: -20 + 20 = 0 0 + -10s = 9 + 20 -10s = 9 + 20 Combine like terms: 9 + 20 = 29 -10s = 29 Divide each side by '-10'. s = -2.9 Simplifying s = -2.9
| 2(x-8)+5=2x-11 | | 112+14x=y | | .5(x-22)=16+5x | | x=300eilrst | | 18+5.50x=11+6.75x | | 6(3s+9)=252 | | x=300liters | | y=4*3-9 | | 9(6+p)=36 | | 6x+16=10x+3 | | 4(a-4)=56 | | 6x+3.5=6.7 | | 4u+8v=-3v+2u | | 10x-1=4x+41 | | 87/y-10=19 | | 6(t+3)=45 | | x-72.5=28.4 | | 6y+12=7y+2 | | 5(n-2)=22 | | 3y=5x-18 | | 3/9*2/5 | | (2-2^3/2)^2= | | 8-7x-3=-59+4x-13 | | 5(x)-20=60 | | http://www.geteasysolution.com/1a-15=4a-3 | | (5x-9)+(10x+10)= | | 8x-6=4x+38 | | 5s-26=59 | | 3y=5x+18 | | y(3y+11)=4 | | 4s+27=91 | | y(3y+11)=11 |